2017
DOI: 10.21873/invivo.11176
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Induces Apoptosis of HSC3 Human Oral Cancer Cells Through Endoplasmic Reticulum Stress and Dysfunction of Mitochondria-mediated Signaling Pathways

Abstract: Abstract. Background Western blotting was used to examine the levels of apoptotic-associated protein and results indicated that fisetin increased expression of pro-apoptotic proteins such as B-cell lymphoma 2 (BCL2) antagonist/killer (BAK) and BCL2-associated X (BAX) but reduced that of anti-apoptotic protein such as BCL2 and BCL-x, and increased the cleaved forms of caspase-3, -8 and -9, and cytochrome c, apoptosis-inducing factor (AIF) and endonuclease G (ENDO G) in HSC3 cells. Confocal microscopy showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 57 publications
(62 reference statements)
0
24
1
Order By: Relevance
“…Cleaved caspase-3 and cleaved caspase-8 expression have been shown to relate with the mitochondria-dependent apoptotic pathway (Zhang et al, 2013 ; Shih et al, 2017 ). In the present study, the activation of caspase-3 and caspase-8 induced by MPP + could be prevented by the pretreatment of Als.…”
Section: Discussionmentioning
confidence: 99%
“…Cleaved caspase-3 and cleaved caspase-8 expression have been shown to relate with the mitochondria-dependent apoptotic pathway (Zhang et al, 2013 ; Shih et al, 2017 ). In the present study, the activation of caspase-3 and caspase-8 induced by MPP + could be prevented by the pretreatment of Als.…”
Section: Discussionmentioning
confidence: 99%
“…Fisetin is the dietary flavonoid and exhibits antioxidant, anti-inflammatory, anti-cancer and neuroprotective activities 37. Recent studies demonstrated that fisetin induces apoptotic cell death through the endoplasmic reticulum stress in human melanoma 38 and mitochondria-dependent apoptotic pathway human oral cancer cells 39. Apoptosis is a morphologically, chemically, and pathophysiologically distinct from necrosis, and the development of cancer treatment can be promoted through understanding the mechanism of apoptosis 40.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro activity of fisetin in the mitochondrial apoptotic pathway has been acknowledged to be effective in the treatment of oral carcinomas. Fisetin enhanced the expression of pro-apoptotic proteins Bak and Bax but reduced anti-apoptotic protein expression (Bcl-2 and Bcl-x), while it also led to activation of caspase-3, caspase-8, caspase-9, and augmented sustained release of cytochrome c and apoptosis-inducing factor expression in HSC3 [51] and SCC-4 oral carcinoma cells [52]. Further, Khan et al found fisetin (10-60 µM) treatment resulted in activation of apoptosis, poly (ADP-ribose) polymerase (PARP) cleavage, modulation of Bcl-2 family protein expression (Bak, Bad, Bid, Bcl-xL), inhibition of the phoshoinositide 3-kinase (PI3K)/Akt signaling pathway, and activation of caspase 3, caspase-9, and-8 enzyme activity in LNCaP prostate cancer cell lines [53].…”
Section: Regulation Of Cancer-related Processesmentioning
confidence: 99%